• Matéria: Matemática
  • Autor: orborous123
  • Perguntado 7 anos atrás

P.(p-a)•(p-b), para p=5,a=1 e b=2

Respostas

respondido por: antoniosbarroso2011
0

Resposta:

60

Explicação passo-a-passo:

Temos que

p.(p - a)(p - b), então

Para p = 5, a = 1 e b = 2, vem que

p.(p - a)(p - b) => 5(5 - 1)(5 - 2) = 5.4.3 = 60.

respondido por: analuor
0

Resposta:

60

Explicação passo-a-passo:

p \times (p - a) \times (p - b) \\ 5 \times (5 - 1) \times (5 - 2) \\ 5 \times 4 \times 3 \\ 60

• Espero ter ajudado.

Perguntas similares